Potensi Daun Kelor (Moringa oleifera) sebagai Agen Anti-Hipergikemia: Studi Literatur : POTENTIAL OF MORINGA LEAF (Moringa oleifera) AS ANTI-HYPERGLICEMIC AGENT: A LITERATUR REVIEW - Kusuma, Ikhwan Yuda; Pujiarti, Yuyun; Samodra, Galih (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2020)
Diabetes mellitus (DM) is a carbohydrate metabolism disorder characterized by high blood sugar levels (hyperglycemia). According to data from the International Diabetes Federation (IDF) 2017, the number of people with diabetes has reached 415 million and is expected to continue to increase in 2040 to around 642 million (55%). One alternative treatment for diabetes is herbal plants, including Moringa oleifera leaves which are rich in nutrients, such as phytochemicals, carotene, flavonoid compounds, phenolic compounds, calcium, iron, protein, vitamins, and contain antioxidants that can stabilize free radicals. So that it can be used as protection against diabetes mellitus. This study aimed to determine the potential of Moringa oleifera leaves in reducing blood sugar levels based on the scientific data collected. This research uses the Literature Review method by searching scientific journals online on the PubMed, Science Direct, and Google Scholar databases published in 2010-2020 with data collection techniques using the PICO approach (Population, Intervention, Comparison, Outcome). The results of reviews in several journals, Moringa oleifera leaves have the potential to significantly reduce blood sugar levels both in experimental and clinical trials; even the use of a combination of metformin and moringa oleifera shows a significant effect on lipid profile, insulin resistance, blood glucose reduction, and significant weight loss compared with metformin alone. This indicates that Moringa leaves are proven to have the effect of lowering glucose levels in the blood.